(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Circuit training is a time-efficient exercise modality that can elicit demonstrable improvements in health and physical fitness. Health related physical fitness is indispensable for every person irrespective of age . Profession and gender to lead a healthy life. One of the key components of health related physical fitness is muscular endurance. The main objective of this very study was to determine influence of circuit training on selected physical fitness variables among college level men volleyball players Sport is a valid physical activity, therefore, given the criteria of increasing its levels for the purpose of improving health; it can be adapted and modified to take into account the target population group. Sports developers have been aware of this for decades as they work at grassroots level across communities from different sectors in society; and have managed to work with the complexity of sport and health promotion. Its simplicity, however, has contributed to the misunderstanding that sporting excellence is at the pinnacle of participation, which can alienate the health-related participant. It is also not compatible with sport can reduce health inequalities; particularly as elite sport carries its own issues of health. Games and sports have crossed many mile stones in the universe.